Implicit Bias, Moods, and Moral Responsibility. (25th August 2017) - Madva, Alex
Abstract: Are individuals morally responsible for their implicit biases? One reason to think not is that implicit biases are often advertised as unconscious, 'introspectively inaccessible' attitudes. However, recent empirical evidence consistently suggests that individuals are aware of their implicit biases, although often in partial and inarticulate ways. Here I explore the implications of this evidence of partial awareness for individuals' moral responsibility. First, I argue that responsibility comes in degrees. Second, I argue that individuals' partial awareness of their implicit biases makes them (partially) morally responsible for them. I argue by analogy to a close relative of implicit bias: moods.